Microparticle‐associated tissue factor activity in patients with pancreatic cancer: correlation with clinicopathological features. (9th February 2013) - Thaler, Johannes; Ay, Cihan; Mackman, Nigel; Metz‐Schimmerl, Sylvia; Stift, Judith; Kaider, Alexandra; Müllauer, Leonhard; Gnant, Michael; Scheithauer, Werner; Pabinger, Ingrid
Abstract: Background: Patients with pancreatic cancer have an unfavourable prognosis. A central role in pancreatic cancer progression has been suggested for tissue factor (TF), the main initiator of the blood coagulation cascade. We hypothesized that elevated levels of plasma microparticle (MP)‐associated TF activity might indicate the presence of poorly differentiated pancreatic cancer, disease dissemination and infiltration of peripancreatic vessels. Methods: MP‐TF activity was measured in 73 pancreatic cancer patients and 22 healthy controls. Abdominal computerized tomography (CT) scans performed at study inclusion were investigated for probability of tumoural vascular invasion. In addition, intratumoural TF expression, D‐dimer and CA 19‐9 levels were determined. Results: MP‐TF activity (pg/mL) was significantly higher in patients (median: 0·37 [range: 0·00–11·91]) than in controls (median: 0·05 [range: 0·00–0·76]; P < 0·001). When pancreatic cancer patients were compared with regard to stage and grade, significantly elevated levels of MP‐TF activity were only present in those with poorly differentiated metastatic nonresectable tumours ( n = 11, median: 2·95 [range: 0·25–11·91]). In three patients with poorly differentiated tumours, a high probability of vascular invasion was found (MP‐TF activity in these cases: 2·95, 7·00 and 10·34). MP‐TF activity correlated strongly with CA 19‐9 (r = 0·60) and weakly with D‐dimer (r = 0·33) levels. Immunohistochemical staining for TF was positive in 14 of 15 resected tumours. MP‐TF activity was associated with an increased risk of mortality (HR: 1·8 per doubling in MP‐TF activity, [95% CI: 1·4–2·4, P < 0·001]). Conclusion: MP‐TF activity might represent a biomarker for a poorly differentiated and invasive pancreatic cancer phenotype and poor survival.